European Database of Explanted UHMWPE Liners from Total Joint Replacements: Correlations among Polymer Modifications, Structure, Oxidation, Mechanical Properties and Lifetime In Vivo - Slouf, Miroslav; Gajdosova, Veronika; Dybal, Jiri; Sticha, Roman; Fulin, Petr; Pokorny, David; Mateo, Jesús; Panisello, Juan José; Canales, Vicente; Medel, Francisco; Bistolfi, Alessandro; Bracco, Pierangiola (Polymers, 2023)
This contribution lays the foundation for the European database of explanted UHMWPE liners from total joint replacements. Three EU countries (Czech Republic, Italy and Spain) have joined their datasets containing anonymized patient data (such as age and BMI), manufacturer data (such as information on UHMWPE crosslinking, thermal treatment and sterilization), orthopedic evaluation (such as total duration of the implant in vivo and reasons for its revision) and material characterization (such as oxidative degradation and micromechanical properties). The joined database contains more than 500 entries, exhibiting gradual growth, and it is beginning to show interesting trends, which are discussed in our contribution, including (i) strong correlations between UHMWPE oxidative degradation, degree of crystallinity and microhardness; (ii) statistically significant differences between UHMWPE liners with different types of sterilization; (iii) realistic correlations between the extent of oxidative degradation and the observed reasons for total joint replacement failures. Our final objective and task for the future is to continuously expand the database, involving researchers from other European countries, in order to create a robust tool that will contribute to the better understanding of structure-properties-performance relationships in the field of arthroplasty implants.
Keywords: micromechanical properties; oxidative degradation; European database; ultrahigh molecular weight polyethylene; UHMWPE; retrieval study; total joint replacements